Female and male Leach's Storm Petrels (Hydrobates leucorhous) pursue different foraging strategies during the incubation period. (6th August 2022) - Mauck, Robert A.; Pratte, Isabeau; Hedd, April; Pollet, Ingrid l.; Jones, Patricia L.; Montevecchi, William A.; Ronconi, Robert A.; Gjerdrum, Carina; Adrianowyscz, Sarah; McMahon, Colin; Acker, Haley; Taylor, Liam U.; et al.
Abstract : Reproduction in procellariiform birds is characterized by a single egg clutch, slow development, a long breeding season and obligate biparental care. Female Leach's Storm Petrels Hydrobates leucorhous, nearly monomorphic members of this order, produce eggs that are between 20 and 25% of adult bodyweight. We tested whether female foraging behaviour differs from male foraging behaviour during the 44‐day incubation period across seven breeding colonies in the Northwest Atlantic. Over six breeding seasons, we used a combination of Global Positioning System and Global Location Sensor devices to measure characteristics of individual foraging trips during the incubation period. Females travelled significantly greater distances and went farther from the breeding colony than did males on individual foraging trips. For both sexes, the longer the foraging trip, the greater the distance. Independent of trip duration, females travelled farther, and spent a greater proportion of their foraging trips prospecting widely, as defined by behavioural categories derived from a hidden Markov Model. For both sexes, trip duration decreased with date. Sex differences in these foraging metrics were apparently not a consequence of morphological differences or spatial segregation. Our data are consistent with the idea that female foraging strategies differed from male foraging strategies during incubation in ways that would be expected if females were still compensating for egg formation.